Hawaiʻi residents' perceptions of Kīlauea's 2018 eruption information - Goldman, Robert; Stovall, Wendy; Damby, David; McBride, Sara (Volcanica, 2023)
The 2018 eruption of Kīlauea Volcano was notable for its variety of large and spatially distinct hazards, simultaneously affecting three geographically disparate, culturally diverse regions in Hawaiʻi. We conducted a pilot study, consisting of 18 semi-structured interviews, two survey responses, and several informal conversations with Hawaiʻi residents to learn which sources/messengers of eruption information were deemed most trusted and credible. Participants' perceptions of the U.S. Geological Survey Hawaiian Volcano Observatory (HVO), community-based messengers, and traditional news media can be examined across four themes: relevance, expertise, sincerity, and pace. Among our interview participants, Lower East Rift Zone (LERZ) residents placed the highest trust in their community messengers, summit residents deemed HVO most trustworthy, and Kaʻū residents trusted information from both HVO and local news media. Our findings suggest that future official eruption communications would benefit from 1) designating communications personnel to act as community liaisons and 2) increasing pace and relevance of information delivery.